The Effect of a Digital-Based Attendance Information System and Work Motivation on Teachers' Work Discipline - Muhammad Farhan Attoillah; M. Syaifuddin; Nunu Mahnun; Kodarni Kodarni (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study is situated within the discourse of educational management, particularly teacher work discipline in relation to the use of digital-based attendance information systems and work motivation. The research problem is grounded in the continued presence of delays in task completion, suboptimal lesson planning, delayed implementation of evaluation, and irregular teacher attendance in school activities. This study aims to analyze the effect of digital-based attendance information systems and work motivation on teacher work discipline at public senior high schools in Kulim District, Pekanbaru, both partially and simultaneously. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 129 teachers and educational staff at SMAN 10 Pekanbaru and SMAN 11 Pekanbaru using a census technique. The novelty of this study lies in its integrated examination of technological and psychological factors in explaining teacher work discipline, whereas previous studies have generally discussed digital attendance systems and work motivation separately. The results show that the digital-based attendance information system has a positive and significant effect on teacher work discipline, with a regression coefficient of 0.333. Work motivation also has a positive and significant effect, with a stronger regression coefficient of 0.601. Simultaneously, both variables have a significant effect, with an Fcount value of 42.990 and a contribution of 40.6%. Academically, these findings strengthen educational management studies by showing that teacher discipline is not only shaped by technology-based monitoring, but also by motivational factors that drive professional responsibility. Therefore, the development of teacher work discipline requires an integrated management approach that combines effective digital supervision with the strengthening of work motivation.